Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire